Prognostic and therapeutic relevance of c‐FLIP in acute myeloid leukaemia. (20th November 2012) - McLornan, Donal; Hay, Jodie; McLaughlin, Kirsty; Holohan, Caitriona; Burnett, Alan K.; Hills, Robert K.; Johnston, Patrick G.; Mills, Ken I.; McMullin, Mary Frances; Longley, Daniel B.
Summary Chemoresistance is a major contributor to the aggressiveness of AML and is often due to insufficient apoptosis. The CFLAR gene is expressed as long and short splice forms encoding the anti‐apoptotic proteins c‐FLIPL and c‐FLIPS (CFLARL and CFLARS, respectively) that play important roles in drug resistance. In univariate analyses of CFLAR mRNA expression in adult AML patients, those individuals with higher than median mRNA expression of the long splice form CFLAR(L) (but not the short splice form) had significantly lower 3 year overall survival (P = 0·04) compared to those with low expression. In cell line studies, simultaneous down‐regulation of c‐FLIPL and c‐FLIPS proteins using siRNA induced apoptosis in U937 and NB‐4 AML cells, but not K562 or OCI‐AML3 cells. However, dual c‐FLIPL/S downregulation sensitized all four cell lines to apoptosis induced by recombinant tumour necrosis factor‐related apoptosis‐inducing ligand (rTRAIL). Moreover, specific downregulation of c‐FLIPL was found to recapitulate the phenotypic effects of dual c‐FLIPL/S downregulation. The histone deacetylase (HDAC)1/2/3/6 inhibitor Vorinostat was found to potently down‐regulate c‐FLIPL expression by transcriptional and post‐transcriptional mechanisms and to sensitize AML cells to rTRAIL. Further analyses using more selective HDAC inhibitors revealed that HDAC6 inhibition was not required for c‐FLIPL down‐regulation. These results suggest that c‐FLIPL may have clinical relevance both as a prognostic biomarker and potential therapeutic target for HDAC inhibitors in AML although this requires further study.